Pengembangan Sistem Diseminasi Prakiraan Cuaca Menggunakan Aplikasi Bot Telegram dengan Metode Webhook - TrI Istiana; Raksaka Indra A; G.S. Budhi Dharmawan; Bowo Prakoso (Elektron : Jurnal Ilmiah, 2020)
An official weather forecast dissemination application named @infoBMKG developed for Android and iOS by BMKG available since 2016. Following users behaviour on instant messaging service application, system development is necessary needed for accommodating request-based dissemination. The Telegram Bot feature with Webhook method is applied because of the efficiency on coding for initial setup in the development of Telegram Bot. Therefore, it allows fast response in sending reply to any request. There are three main menus in the design of the telegram Bot (@BMKGbot) displayed as Weather Forecast, Airport Weather, and Satellite Imagery. As results of performance testing, the average response time dissemination-request 2.54s for Weather Forecast, 2.76s for Airport Weather and 7.28s for Satellite Imagery. Bigger size of data disseminated in an image format of satellite imagery cause longer response time, however the performance testing obtain response times within satisfactory period and meet as expected. It is recommended to implement @BMKGbot at reliable hosting service on its operational environment for chasing users’ satisfaction with high availability services in term of weather forecast dissemination.